Does Financial Innovation Drive Firm Value? The Mediating Role of Financial Performance in Indonesian Banking - Mursidah Nurfadillah; Fenty Fauziah; Nidya Rudiani; Nur Hanisfatin Rushami Zien (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Financial innovation in Indonesian banking has evolved alongside changes in the banking system. While the adoption of Internet Banking (IB) services has been fast, bank value indicators, like Price-to-Book Value (PBV), have shown significant fluctuations, raising questions about whether financial innovation truly adds value. Objective: This study examines the impact of financial innovation on firm value and financial performance in Indonesian banks, and whether financial performance mediates this relationship. It views financial innovation not only through its financial outcomes but also as part of the broader technology-driven digital transformation in banking towards sustainability and resilience. Methods: The research was conducted by analyzing Secondary data from 13 banks listed on the Indonesia Stock Exchange (BEI) annual financial report data with the period of 2019–2024 which were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Results: Financial innovation directly affects firm value, but does not directly affect financial performance that can be used to significantly mediate the relationship between financial innovation and firm value. What this means is that, rather than an immediate profitability boost, the additional value to the firm from financial innovation is likely due to a long-term perspective of growth potential and viability. Conclusion: Market participants value innovation not just for short-term financial gains, but for its role in building resilience and long-term business models. While some innovations may offer short-term benefits, they remain a key strategy for enhancing firm value and building trust in the market over time.